PENGARUH ALOKASI BELANJA MODAL DAN PERTUMBUHAN EKONOMI TERHADAP INDEKS PEMBANGUNAN MANUSIA DI KABUPATEN/KOTA RIAU - Asepma Hygi Prihastuti (Menara Ilmu, 2018)
The high and low Human Development Index (HDI) is influenced by several factors, such aseconomic growth, infrastructure and government policies. Infrastructure is built by the statethrough capital expenditure. The purpose of this study is to determine the effect of capitalexpenditure allocation and economic growth to human development index in Riaudistrict/city 2014-2016. Data processing by path analysis using SPSS version 21. The resultof research shows that capital expenditure allocation has direct influence to economicgrowth in district/city of Riau Province. The allocation of capital expenditure does not have adirect impact on the human development index, while the economic growth directly affectsthe human development index. And the allocation of capital expenditures indirectlysignificantly influence the Human Development Index through economic growth.Keywords: allocation of capital expenditure, economic growth, Human Development Index(HDI)